Pengaruh Latihan Ball Feeling terhadap Kemampuan Dribbling pada Atlet Sekolah Sepakbola (SSB) - Dona Pebrima; Muhammad Suhdy; Hengky Remora (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2021)
This study aims to determine whether there is an effect of ball feeling training on the dribbling ability of YF13 soccer school (SSB) athletes in Lubuklinggau City. The research method used in this study was quasi-experimental. The data was collected using the technique of soccer dribbling ability test, followed by analysis using t-test. The results showed the value in ttable> alpha with a value of `20,843>2,10. From these results, it can be said that there is an influence because the tcount is greater than talpha. In conclusion, ball-felling training on the dribbling skills of YF13 football school (SSB) athletes in Lubuklinggau City in 2020. Keywords: Ball feeling, Dribbling